The Development of Character Education Curriculum Model for Madrasah Ibtidaiyah In Muaro Jambi - Yogia Prihartini; Wahyudi Buska; Rapiko Rapiko; Nurazmi Aziz (IJER (Indonesian Journal of Educational Research), 2020)
This research aims to provide a valid character education for grade schools. This research was done due to the ineffectiveness of character education and development in grade schools. This developmental research was done using the ADDIE model with five phases; analysis of needs, product design, product development, implementation and evaluation of the research product. Data collection was done using an observational guide, interview, and documentation for curriculum designing, and questionnaires which will then be analyzed in order to find out the condition of current character education. Samples were chosen using a purposive sampling method, and the data was qualitatively and quantitatively processed. The research result shows that the current character education can be considered as good. The designed character education curriculum was validated by the curriculum, material, and language experts. Validation result shows that the curriculum is valid with minor revision. Field implementation shows that character education curriculum is practical. The curriculum’s effectiveness was tested using test result from selected schools. At SDN/MIN Pematang Gajah, the achieved criteria are considered as high with 98% lesson completion, at SDN/MIN Sebapo and SDN/MIN Tarikan the achieved criteria is considered as moderate with 75% and 78% lesson completion rate. Teacher’s book practicality was deemed as practical with a general score of 4,5.